Power Hardware-In-the-Loop simulation for testing multi-source vehicles. Issue 1 (July 2017) - Castaings, A.; Bouscayrol, A.; Lhomme, W.; Trigui, R.
Abstract: Energy management of multi-source vehicles is a complex task. The higher the number of sources becomes, the higher the complexity is. Moreover, the energy management strategies have to face real-time issues. As a consequence, it is important to find some testing procedures to assess the developed strategies, in real-time conditions before implementation in the vehicle. In this paper, a Power Hardware-In-The-Loop simulation is implemented for a Fuel Cell – battery – Supercapacitors vehicle. The set-up enables to test some Energy Management Strategies in real-time conditions.